(untitled) (Bangladesh Journal of Medical Science, 2019)
Objective: Early neonatal mortality within the ﬁ rst 24 hours contributes substantially to overall neonatal mortality rates. Reliable cause- specific mortality data are limited; thus the estimated proportion of prematurity-related deaths nationally remains questionable. The objective was to determine the presumed causes of neonatal death within the ﬁ rst 24 hours in Ad-din Medical College Hospital. Methods: This is a retrospective study initiated in January of 2016 to December 2016, conducted in the delivery room and adjacent neonatal area at Ad-din Medical College Hospital. Research assistants were trained to observe and record events related to labor, neonatal resuscitation, and 24-hour postnatal course. Perinatal asphyxia (PNA) was defined as failure to initiate spontaneous respirations and/or 5-minute Apgar score <7, prematurity as gestational age <37 weeks, and low birth weight (LBW) as birth weight (BW) < 2500gm. Data were analyzed with using the SPSS version (Chi-Square test). Results: Over 1 year, 14316 neonates were born and evaluated. Of these, 1867 were admitted to the neonatal area. Twenty seven neonates died secondary to Prematurity (55.56%), PNA (37.03%) and Meconium aspiration syndrome (7.41%). Conclusions: Most cases of early neonatal mortality were related to Prematurity and its related complications and Perinatal asphyxia are additional important considerations. Reducing Perinatal mortality requires a multifaceted approach with attention to issues related to potential complications of Prematurity and its related complications and PNA. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.593-597